Klitih and Street Crimes: Why Juvenile Involved in Crime? - Putri, Siti Ameenah; Faradina, Ginar Listya; Sabri, Ahmad Zaharuddin Sani Ahmad; Putri, Laras Widayati (Faculty of Law, Universitas Negeri Semarang, 2023)
The spectrum of crimes within society is becoming increasingly diverse. Notably prevalent among them are street crimes perpetrated by teenagers, commonly known as